Vulnerability assessment of debris flow in the central Peruvian rainforest – An intercultural approach - Luis Izquierdo-Horna; Angelica Sánchez-Castro; Jose Duran (Heliyon, 2023)
For several decades, calamitous debris flows have inflicted profound negative impact on Peruvian rainforest society, encompassing both economic losses and human casualties. To address this concern, this study proposes a methodological tool to assess vulnerability while focusing on intercultural nuances. The contextual analysis of the incident reports identifies La Merced (Junín, Perú) as a severely affected locality, thereby justifying its selection for a detailed case study on the Pampa del Carmen sector. The study conducted a thorough systematic review of parameters such as diglossia, poverty, and origin that are crucial for vulnerability assessment. Moreover, these parameters aided in developing a structured digital survey. The integration of survey data into the analytic hierarchy process revealed high levels of vulnerability in the sector, emphasizing the imminent need for targeted interventions. The intercultural approach is significant as it facilitates future risk mitigation strategies based on effective integration and genuine acknowledgment of social dynamics and individual freedoms within the region for devising impactful risk management policies and plans.